Comparative Effects of Extracts from Black Rice or Pathum Rice Combined with Cereals on Blood Glucose Levels, Serum Insulin Levels and Blood Chemistry in Diabetic Rats - Sakuljaitrong, Supasorn; Buddhakala, Nopparat; Yongkhamcha, Butsara; Sarakul, Orathai; Tongaram, Yaowapar; Asawawibul, Sasiprapha; Buddhakala, Moragote (Trends in Sciences, 2024)
Rice is one of the major cereal crops in several Asian countries. It contains a variety of nutrients and provides valuable health benefits. The antidiabetic activity of rice combined with cereals has not been studied. Therefore, the present study was carried out to determine and compare the effects of extracts from Black rice (BRE), Pathum rice (PTRE), Black rice combined with cereals (BRCE), and Pathum rice combined with cereals (PTRCE) on body weight, blood glucose levels, serum insulin levels and blood chemistry of Streptozotocin (STZ)-induced diabetic rats. The results revealed that BRCE exhibited the highest activity in reducing fasting blood glucose (FBG) levels and increasing serum insulin levels, and also recovered the lipid profiles, renal function and hepatic function resulting from STZ in the diabetic rats, followed by BRE, PTRCE and PTRE, respectively. Also, BRCE exhibited an activity with similar potential to Glibenclamide. The findings indicate that the rice extracts possess antidiabetic activity which exerts the activity by increasing serum insulin resulting in reduction of blood glucose. Rice combined with cereals provides better antidiabetic activity and could be a source of valuable antidiabetic materials. HIGHLIGHTS Extracts from Black rice and Pathum Thani fragrant rice exhibit antidiabetic activity in Streptozotocin-induced diabetic rats. Antidiabetic activity of the extracts from Black rice and Pathum Thani fragrant rice is due to an increase in insulin secretion. Black rice exhibits antidiabetic activity higher than Pathum Thani fragrant rice. Combination with cereals could enhance the antidiabetic activity of rice. The extracts from Black rice and Pathum Thani fragrant rice may be useful for the management of diabetes mellitus. GRAPHICAL ABSTRACT